2003
DOI: 10.1163/22941932-90000344
|View full text |Cite
|
Sign up to set email alerts
|

Changes Caused by Mid-Rotation Fertilizer Application to the Fibre Anatomy of Pinus Radiata

Abstract: Effects of nitrogen (N) and phosphorus (P) fertilizers on average fibre radial diameter, tangential diameter, wall thickness and number of fibres per unit area were studied over 7 years of growth in radiata pine. Stands were in mid-rotation, thinned and treatments replicated 4 times at 3 sites. Compared to a thinned, unfertilized control, N decreased and P increased fibre radial diameter. Only N decreased fibre radial diameter, thereby increasing the number of fibres per unit area. All fertilizer treatments de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
4
10
1
3
Order By: Relevance
“…Similarly, Hannrup et al (2001) previously observed in Scots pine a positive weak correlation between wood density and fibre length for juvenile wood, but not in mature wood, where it was negative or even non-existent. In other pine species such as Maritime pine or radiata pine (Pinus radiata), negative correlations have also been observed previously between wood density and fibre length or width, for example (Nyakuengama et al 1999, 2003, Pot et al 2002.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, Hannrup et al (2001) previously observed in Scots pine a positive weak correlation between wood density and fibre length for juvenile wood, but not in mature wood, where it was negative or even non-existent. In other pine species such as Maritime pine or radiata pine (Pinus radiata), negative correlations have also been observed previously between wood density and fibre length or width, for example (Nyakuengama et al 1999, 2003, Pot et al 2002.…”
Section: Discussionsupporting
confidence: 53%
“…Even though trees have started producing outerwood at mid-rotation, the application of nitrogen increases the number of tracheids for a given area, with a concomitant reduction in tracheid radial diameter, and wall thickness [89]. Wood properties are negatively affected, but the response depends on the rate of fertilizer applied, site conditions, and age of the stand.…”
Section: Mid-rotation Thinning and Fertilizationmentioning
confidence: 99%
“…En Arena hoemeda resultaron mayores que los registrados en el sitio Arcilla. Estas diferencias difieren con lo determinado en Pinus radiata en Chile (Melo et al (1988) pero son coincidentes con otros estudios realizados en Pinus radiata en diferentes sitios (Burdon 1975;Nyakuengama et al 2003).…”
Section: Diámetro De Traqueidas (1/diámetro 2 )unclassified
“…Las diferencias significativas que se registraron entre los dos sitios concuerdan también con lo informado por diversos autores (Melo et al 1988;Nyakuengama et al 2003;Dúchense y Zhang 2004;Moltenberg, M∅ib∅ 2006) El largo de traqueidas resultó afectado, además del sitio, por la edad. Este efecto está asociado a la actividad periódica del cambium y es especialmente importante en los primeros años.…”
Section: Largo De Traqueidasunclassified